2016
DOI: 10.18632/oncotarget.12218
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Profilin-1 suppresses cell adhesion and tumor growth via predicted alterations in integrin and Ca2+ signaling in T24M-based bladder cancer models

Abstract: Bladder cancer (BC) is the second most common malignancy of the genitourinary system, characterized by the highest recurrence rate of all cancers. Treatment options are limited; thus a thorough understanding of the underlying molecular mechanisms is needed to guide the discovery of novel therapeutic targets. Profilins are actin binding proteins with attributed pleiotropic functions to cytoskeletal remodeling, cell adhesion, motility, even transcriptional regulation, not fully characterized yet. Earlier studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
1
15
0
2
Order By: Relevance
“…13,21 Similarly, Pfn1 fl/fl-Pf4Cre platelets showed severely delayed and less effective clot retraction ( Figure 1H), further reflecting impaired integrin function and actin dynamics. 10,13 Because Pfn1 is an effector of the RhoA/ Rho-associated kinase (ROCK) pathway, these findings are in agreement with reports on RhoA-deficient platelets that show abolished clot retraction.…”
Section: Pfn1mentioning
confidence: 91%
See 2 more Smart Citations
“…13,21 Similarly, Pfn1 fl/fl-Pf4Cre platelets showed severely delayed and less effective clot retraction ( Figure 1H), further reflecting impaired integrin function and actin dynamics. 10,13 Because Pfn1 is an effector of the RhoA/ Rho-associated kinase (ROCK) pathway, these findings are in agreement with reports on RhoA-deficient platelets that show abolished clot retraction.…”
Section: Pfn1mentioning
confidence: 91%
“…Animals, flow cytometry, aggregation, immunostaining, adhesion under flow, clot retraction, immunoblotting, tail bleeding assay, in vivo model, Ca 21 measurements, atomic force microscopy, and statistical analyses are described in the supplemental Methods. 13 Animal studies were approved by the district government of Lower Franconia (Bezirksregierung Unterfranken).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shRNA sequences targeting EIF3D and RHEB were 5′-CCGGCCTCAGACATACTCCATAGATCTCGAGATCTATGGAGTATGTCTGAGGTTTTTG-3′, respectively. A scrambled shRNA (shscramble) was used as control, as previously described [ 119 ]. For the lentivirus production, a four plasmid system was used for the transient transfection of 293T cells as previously described [ 120 , 121 ], followed by concentration with Amicon Ultra Centrifugal Filters-100K Units (Merck Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, a recent study reported downregulation of cell-surface integrin b1 expression and Wnt signaling in a bladder cancer cell line upon knockdown of Pfn1 expression. 28 While this may suggest apparent contradictory effects of Pfn1 knockdown between breast and bladder cancer cells, because of differences in experimental parameters between the 2 studies (e.g., surface protein expression vs mRNA level of integrin b1) it is difficult to reconcile these results. Cell-specific differences in the results will not be totally surprising given that Pfn1 has context-specific effects in normal vs cancer cells and even between different cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%